Reconstruction of the hypoplastic nasal Alar with an auriculare composite graft - M Khakzad (Babol University of Medical Sciences, 2003)
Background and Objective: The congenital anomaly of nose is the one of causes of cosmetic of face and repair of this defect is very difficult. In this article, it was reported a case of congenital hypoplastic nasal Alar with failure in operation two times. Case: A 19-year-old female referred with hypoplastic nasal Alar who had been already operated two times with a failure in repairing this defect. A composite graft from ear with suitable size was inserted in the defect area of nose and it was improved. Conclusion: For repairing this anatomical defect and decreasing failure, this new surgical method is suggested.